DOSIS PUPUK KANDANG DAN UMUR PANEN PADA PRODUKSI BABY KANGKUNG (IPOMOEA REPTANS) - Leviana Eka Vivia; Trijono Djoko Sulistyo; Mujiyo Mujiyo (Universitas Sebelas Maret, 2017)
The research aims to assess the yield of baby kale that can be consumed almost all of the parts and generate organic manure free. Field research was conducted in Sindon Village, Ngemplak, Boyolali in September to October 2016. The research method uses Randomized Complete Block Design factorial with two factors, these are the dosage of manure and the age of harvest. Manure consisted of 4 doses O1 (0 ton/ha), O2 (6 tons/ha) and O3 (8 tons/ha) and O4 (10 tons/ha), and age of harvest consisted of P1 (16 DAS), P2 (20 DAS), and P3 (24 DAS). Variables observed were plant height, number of leaves, internode length, fresh weight, dry weight, leaf area index, and harvest index. The result showed that age of harvest has significant influence plant height, internode length, the number of leaves, leaf area index, fresh weight, dry weight, and harvest index. Manure doses only influence dry weight. Manure dosage of 8 ton/ha and harvest age of 16 DAS is the best combination of baby kale. Manure dosage of 10 ton/ha and harvest age of 16 DAS produce baby kale that can be consumed almost in all parts of the plant with the highest harvest index that is equal to 0.83.